Tempo de concentração em pequena bacia hidrográfica parcialmente urbanizada em Uberlândia - MG - Silveira, Liliana Batista Parreira (2016)
The time of concentration is defined as the time required for the entire area of the watershed contribute to the surface runoff in a checkpoint, being very useful to visualize the hydrological response. Therefore, the present studywas objective to estimate the time of concentration theBacia Hidrográfica Experimental do Córrego Glória, em Uberlândia-MG,which has an area of 8,27 km2, by means ofhydrograph. In addition, the objective of this study was to compare the values time of concentration observed in hydrographs with those estimated by empirical methods. Finally, this work also sought tomodel a mathematical equation capable of estimating the time of concentration for the basin in question, based on hydrological variables related to rainfall.In this study, time of concentration was estimated from twelvehydrograph obtained in the watershed studied,out of a total of seventeen,from a single block excess rainfall. After this, were determinedinflections in parts ascending and descending of the hydrographs based on the flow. The time elapsed between the end of the effective rainfall and inflections descendingwas considered as time of concentration. After obtaining the time of concentration in the various precipitation events. Such values were compared with 22 empirical methods described in the literature for estimating the time of concentration. The determination of the time of concentration by means of empirical formulas is subjectto the inaccuracies and uncertainties that are due to the type of runoffthat each formula seeks to represent and to the place where it was developed. In this sense, we tried to model a mathematical equation that best estimates the concentration time for the watershed in study. The results showed that the mean basin time of concentration was 172 minutes. The equation for estimating the time of concentration that presented the best result was SCS Lag, in cases where rain intensity data are not available. When this variable is available, it is recommended to use the Kinematic Wave Equation. The equation for estimating time of concentration Bacia Hidrográfica Experimental do Córrego Glória showed up consistent and with good precision, getting 0,76 and 0,88 for the determination coefficients and Nash-Sutcliffe, respectively.